2023
DOI: 10.1101/2023.05.19.23290208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing changes in incubation period, serial interval, and generation time of SARS-CoV-2 variants of concern: a systematic review and meta-analysis

Abstract: Background: After the first COVID-19 wave caused by the ancestral lineage, the pandemic has been fueled from the continuous emergence of new SARS-CoV-2 variants. Understanding key time-to-event periods for each emerging variant of concern is critical as it can provide insights into the future trajectory of the virus and help inform outbreak preparedness and response planning. Here, we aim to examine how the incubation period, serial interval, and generation time have changed from the ancestral SARS-CoV-2 linea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 174 publications
0
1
0
Order By: Relevance
“…A previous study examined the global evolution rate of SARS-CoV-2 during the early stages of the outbreak and reported an estimated mean nucleotide mutation rate ranging from 1.79 × 10 −3 to 1.83 × 10 −3 substitutions per site per year [ 29 ]. In another study, it was suggested that the incubation period, serial interval, and generation time of SARS-CoV-2 have progressively decreased with the emergence of each new VOC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study examined the global evolution rate of SARS-CoV-2 during the early stages of the outbreak and reported an estimated mean nucleotide mutation rate ranging from 1.79 × 10 −3 to 1.83 × 10 −3 substitutions per site per year [ 29 ]. In another study, it was suggested that the incubation period, serial interval, and generation time of SARS-CoV-2 have progressively decreased with the emergence of each new VOC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%